2012
DOI: 10.1111/j.1365-2117.2011.00539.x
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of the high‐elevated depocenters of the northern Sierras Pampeanas (ca. 28˚ SL), Argentine broken foreland, South‐Central Andes: the Pipanaco Basin

Abstract: The Pipanaco Basin, in the southern margin of the Andean Puna plateau at ca. 28°SL, is one of the largest and highest intermontane basins within the northernmost Argentine broken foreland. With a surface elevation >1000 m above sea level, this basin represents a strategic location to understand the subsidence and subsequent uplift history of high‐elevation depositional surfaces within the distal Andean foreland. However, the stratigraphic record of the Pipanaco Basin is almost entirely within the subsurface, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 80 publications
1
21
0
Order By: Relevance
“…This episode temporally matches the formation of the foreland landscapes in Peru and Argentina (Espurt et al, 2007;Dávila et al, 2012) ). The subduction angles vary along strike from flat (0˚) to a typical (30˚) for South America and the density contrasts (∆) of the slab (with respect to the mantle) are controlled by the slab age, the inferred crustal thickness and the Benioff zone geometry ( Fig.…”
Section: Methodssupporting
confidence: 63%
See 1 more Smart Citation
“…This episode temporally matches the formation of the foreland landscapes in Peru and Argentina (Espurt et al, 2007;Dávila et al, 2012) ). The subduction angles vary along strike from flat (0˚) to a typical (30˚) for South America and the density contrasts (∆) of the slab (with respect to the mantle) are controlled by the slab age, the inferred crustal thickness and the Benioff zone geometry ( Fig.…”
Section: Methodssupporting
confidence: 63%
“…1b): the Sierras Pampeanas broken foreland (often used as a modern analogue for the US Laramide, Jordan and Allmendinger, 1986). The Sierras Pampeanas are isostatically uncompensated and have associated high-elevation depocenters >1 km above sea level (Dávila et al, 2012). These features date to the latest Miocene-Pliocene, coeval with the advent of flat subduction (Ramos, 2009).…”
mentioning
confidence: 99%
“…Bense et al () have suggested that most of the relief formation and rock exhumation took place during the Permo‐Triassic based on thermal modeling of these old thermochronologic ages. In contrast, several studies have proposed Miocene relief development based on the Miocene stratigraphic record and thermal modeling (Bense et al, ; Davila et al, ; Mortimer et al, ; Sobel & Strecker, ; Zapata et al, ).…”
Section: Geological Backgroundmentioning
confidence: 99%
“…1000 m a.s.l. ), located in the northern part of the Sierras Pampeanas (Dávila et al 2012) (Fig. 1B).…”
Section: Main Environmental Features and Processes Of The Inland Salimentioning
confidence: 99%
“…1B). It is an intermontane hydrological system of about 10,000 km 2 , where the presence of a tangential fluvial system (Colorado River) gives it a more complex character (Vervoorst 1954;Sosic 1973;Morlans 1995;Zarantonello and Mamani 1999;Alonso 2006;Dávila et al 2012). This basin is the groundwater discharge area of an important hydrographic network, making its aquifers valuable resources (Sosic 1973).…”
Section: Main Environmental Features and Processes Of The Inland Salimentioning
confidence: 99%